Evaluation of Certain Inflammatory Markers in Transfusion Dependent β- Thalassemic Patients - Mohammed Mahmoud, Sameer (Tikrit Journal of Pharmaceutical Sciences, 2025)
To determine the serum concentration of certain inflammatory markers including TNF-α and hs-CRPβ-thalassemic patients on different types of treatmentand to investigate the possible correlation between these inflammatory markers and iron overload referred to by serum ferritin concentration, moreoverto assesswhether inflammation in β-thalassemia could be controlled by deferasirox or deferoxamine as compared to transfusion dependent patients without iron chelator. Ninety transfusion dependent β-thalassemic children with age range 13–75 months were included in this study, and 30 age and sex matched healthy subjects served as control,thepatients were divided into three groups according to the type of the treatment,each group included 30 patients Group1 comprised β-thalassemic patients without iron chelator, Group2 comprisedβ-thalassemic patients on deferasirox iron chelator while Group3 comprisedβ-thalassemic patients on deferoxamine iron chelator. Serum ferritin, hs-CRP, and TNF-α was measured for all participants by ELISA method. Compared with the control, the serum level of ferritin and hs-CRP were significantly elevated in all patients groups while the serum level of TNF-α were only significantly elevated in Group1 and Group3. Further analysis of the results revealed positive correlation between serum ferritin withTNF-α and with hs-CRP.A comparison among the patients groups show that patients on deferasirox (Group2) had significantly low level of TNF-α as compared to Group1 and Group3. On the other hand serum ferritin and hs-CRP concentration in Group3 were significantly higher than the other two groups, furthermore when Group3 patients are subdivided according to their compliance on deferoxaminethe result show that the serum level of ferritin, hs-CRP and TNF-α are significantly higher in poor compliance subgroup as compared to good compliancepatients and when good compliance subgroup are compared with Group2 no significant deference in the measured parameter was found. Chronic inflammatory state is present in these patients withincreased levels of inflammatory markers such as TNF-α andCRP. The observed correlations of ferritin with inflammatory markers imply that iron overload may play a key role in release of these markers. Chelation Therapy with deferasirox can attenuate inflammation and reduces inflammatory markers level while deferoxamine appear to be less effective as most patients suffer from poor compliance on this type of iron chelator